2021
DOI: 10.3126/ajms.v12i4.33136
|View full text |Cite
|
Sign up to set email alerts
|

Study on Human Cranial Index with its Sex Difference from Central Kerala

Abstract: Background: Cranial index, primarily used as an indicator of race had been studied by various workers in view of its morphometric difference in sex prediliction. Hence it would be useful to identify sex of an individual from skeletal remains. Similar studies from our geographic region, if at all present might be very few. Aims and Objective: Based on maximum breadth and length of skull the study aimed at whether there was any statistically significant difference in the cranial index of male and female.&#… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
0
1
Order By: Relevance
“…With the exception of maximum cranial breadth, the values of the other linear variables (MCL, BZB, MFB and UFH) in our study was higher that the values reported by Senol et al [1] The value of the cranial index (CI) in our study was comparable (or higher) than reports from several works in India [8,13,17] (Table 5). However, it was lower than the values reported from works done in Turkey [1] and Thailand [10].…”
Section: Discussioncontrasting
confidence: 56%
“…With the exception of maximum cranial breadth, the values of the other linear variables (MCL, BZB, MFB and UFH) in our study was higher that the values reported by Senol et al [1] The value of the cranial index (CI) in our study was comparable (or higher) than reports from several works in India [8,13,17] (Table 5). However, it was lower than the values reported from works done in Turkey [1] and Thailand [10].…”
Section: Discussioncontrasting
confidence: 56%